Criminal Punishment Policy For Perpetrators of Digital Pornographic Content Distribution Through Social Media From A Contemporary Criminal Law Perspective Based On Pornography Law - Jefryanta, Jefryanta; Sudiro, Amad (Dinasti Research, 2025)
The development of digital technology has facilitated the distribution of pornographic content through social media, creating new challenges for criminal law enforcement. This phenomenon demands adaptive and proportional criminal policies based on contemporary criminal law principles and the provisions of Law Number 44 of 2008 concerning Pornography. The problem faced is how to regulate criminal policies for perpetrators of the distribution of digital pornographic content through social media in Indonesia and how to construct criminal policies for the distribution of digital pornographic content through social media in Indonesia. The research method used in this study is normative juridical legal research. The results of the study indicate that the regulation of criminal policies for perpetrators of the distribution of digital pornographic content through social media in Indonesia is regulated in Law Number 44 of 2008 concerning Pornography and supported by the Information and Electronic Transactions (ITE) Law, but its implementation still requires harmonization to be more effective and adaptive to developments in digital technology. Meanwhile, the construction of criminal policies for the distribution of digital pornographic content needs to be directed towards a more comprehensive approach, by balancing aspects of law enforcement, protection of public morals, and the right to freedom of expression within the framework of contemporary criminal law.